FORMULATION AND PHYSICAL QUALITY TESTING OF MORINGA LEAVES AND GINGER COMBINATION TEA BAGS IN AN EFFORT TO LOWER BLOOD PRESSURE - Pramita Yuli Pratiwi; Sugit Tri Ambarwanto; Titik Lestari; Irma Wati Ngadimon (Poltekkes Kemenkes Surakarta, 2025)
Functional foods, including functional beverages, play a crucial role in public health, including lowering blood pressure. In addition to health and nutritional aspects, food quality can be determined by its taste and the quality of natural ingredients. One such product is tea bags made from moringa leaves and ginger. Flavonoids, a secondary metabolic compound in moringa leaves and ginger, can be beneficial for health. This study aimed to determine the optimal formulation and to conduct physical quality tests on a combination of moringa leaves and ginger tea bags using two formulas. The tea bag formula used was a combination of moringa leaves and ginger with a ratio of F1 (2:1) and F2 (1:2). Physical quality tests were conducted in the form of pH, water content, organoleptic, and hedonic tests on 20 respondents. The results of the organoleptic test showed that F1 had a brown color, a moringa flavor with a ginger sensation, and a distinctive moringa odor, while F2 had a brown color, a ginger flavor with a moringa sensation, and a distinctive moringa odor. The pH test showed that F1 had a pH of 6.07, while F2 had a pH of 6.52. The water content test showed F1 results of 0.91% and F2 1.45%. The hedonic test showed that F1 preferred color, F2 preferred aroma, and F2 preferred taste. This study concludes that the physical quality tests of F1 and F2 are in accordance with the established quality standards, while the hedonic test preferred F2 with a percentage of color, aroma, and taste of 52.27%.